The transition to a teaching hospital: Patient satisfaction before and after the introduction of medical students. (August 2014) - Esguerra, Roberto; Toro, Jaime; Ospina, José Miguel; Porras, Alexandra; Díaz, Camilo; Reyes, Saúl
Abstract: Background : Several studies have explored the effect of the presence of medical students on patient satisfaction. However, nearly all of these studies took place in hospitals where medical students had been involved in patient care for many years. Less is known about patients' perceptions of care in a hospital moving toward becoming a teaching facility with undergraduate students. No research has explored patient satisfaction before and after the introduction of medical students. Objective : To assess patient satisfaction as an indicator of quality of care (QoC) from the patients' perspective, before and after the presence of medical students in a general hospital setting. Methods : This observational, cross-sectional study was conducted at Hospital Universitario–Fundación Santa Fe de Bogotá (HU–FSFB) in Bogotá, Colombia. The study had two phases. In 2006, prior to HU–FSBF becoming a teaching hospital, 385 subjects were asked to fill out a closed-question questionnaire addressing patients' satisfaction and perception of QoC provided by attending physicians. During the second period in 2009, 372 patients answered the same questionnaire when medical students were involved in their care. Results : Patients' perceptions of QoC provided by attending physicians improved in five aspects when medical students were present: friendliness ( p = 0.003), competence providing medical care ( p = 0.049), quality of information provided ( p = 0.025), amount of time spent with the patient ( p < 0.001) and availability to personally provide care ( p < 0.001). Overall patient satisfaction also significantly increased ( p < 0.001). Conclusions : The presence of medical students does not negatively affect patients' perceptions of QoC, on the contrary, these results provide evidence of improved patient satisfaction in several aspects of care when medical students were involved. The relevance of this study lies in its unique way of comparing patient satisfaction before and after the introduction of medical students. This setting helps elucidate the real effect of the presence of medical students on patient satisfaction.